Watering cattle (young bulls) with brackish water – a hazard due to its salt content? - Visscher, C. F.; Witzmann, S.; Beyerbach, M.; Kamphues, J. (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2013)
Objective: The aim of this experimental study was primarily to test the effects and reactions of cattle offered salty water as the only source of drinking water. Material and methods: Mineral balance studies were carried out on three bull, continuously fed a ration based on hay, hay cobs, barley, soybean meal and a vitamin/mineral supplement. The salt content of the drinking water varied between the trials (trials I/II/III: 0.10/5.00/10.0 g/l; town water supplemented by different amounts of an additive containing 95.4% sodium chloride and 4.6% potassium chloride). Results: Rising salt concentration of the drinking water led to significantly higher sodium, potassium and chloride intake (sodium: trial I/II/III = 5.42/59.5/ 157 g/day; potassium: trials I/II/III = 108/117/121 g/day; chloride: trials I/II/III = 22.8/112/266 g/day) mainly caused by a significantly higher water intake (trials I/II/III: 21.8 ± 2.03/30.4 ± 3.08/41.5 ± 5.89 kg/day). Amounts of urine increased significantly (trials I/II/III: 3.99 ± 0.46/ 9.66 ± 1.34/20.2 ± 3.14 kg/day). The concentrations of minerals in the urine (sodium: trials I/II/III = 123/3729/6705 mg/kg; potassium: trials I/II/III = 17345/9996/ 5496 mg/kg; chloride: trials I/II/III = 2020/ 9672/11870 mg/kg) and faeces (sodium: trials I/II/III = 1299/6544/ 7653 mg/kg; potassium: trials I/II/III = 6343/3719/3490 mg/kg; chloride: trials I/II/III = 3851/4580/4693 mg/kg) also changed significantly over time. Serum values of sodium tended to decrease (trials I/II/III: 142/137/137 mmol/l) within the phsiological range, whereas those of chloride increased (trials I/II/III: 91.5/95.6/97.5 mmol/l) at higher salt concentrations in drinking water. The haematocrit, pH-value as well as urea content in blood were not affected by the higher salt intake. In balance trial III (highest salt load: 10.0 g/l), sodium intake of the bulls reached 0.57 ± 0.03 g/kg BW (~22.1 ± 0.9 g sodium/kg dry matter feed). Conclusion and clinical relevance: An increase of salinity in drinking water up to 10 g/l – with otherwise harmless water quality – had no measurable negative effects on animal health in the investigation period and subsequent periods (total of 58 days with more than 5.00 g of salt per litre drinking water).
Keywords: Grazing cattle; brackish water; salt intake; salt water tolerance